Does occupational exposure to fentanyl cause illness? A systematic review - Adams, Axel; Maloy, Caitlin; Warrick, Brandon J. (Clinical toxicology (Philadelphia, Pa.), 2023)
The opioid epidemic in the United States continues to result in an increasing number of deaths and is increasingly dominated by fentanyl and fentanyl analogs. As a result, first responders are likely to come into contact with fentanyl-containing substances daily. Concerns persist regarding occupational exposure resulting in intoxication. We performed a systematic review to describe occupational illnesses from fentanyl and its analogs. We conducted a systematic review of the literature following the 2020 Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines to assess the danger of occupational exposure to fentanyl. The PubMed, EMBASE, Google Scholar, SCOPUS, CINAHL, and National Institute for Occupational Safety and Health databases were queried to identify occupational fentanyl exposures. Studies included were single case reports, case series, observational studies, controlled studies, and abstracts from scientific presentations. We reviewed articles meeting the eligibility criteria and abstracted outcome data. Outcomes included study design, number of study subjects and study demographics, description of exposure, personal protective equipment used, duration of symptoms, illness developed, medical evaluation performed, treatment provided, hospitalizations, deaths, drug testing performed, and any situation review performed to prevent illness, analytical confirmation of the identity of culprit agent, and concentrations of drug in serum/blood. Our search yielded 454 citations after deduplication. After abstract and text review, 12 unique reports met the inclusion criteria. All identified studies were observational studies. Ten of the 12 were Health Hazard Evaluation reports from the National Institute for Occupational Safety and Health; two reports describe the same exposure case. There were no reported instances of comprehensive drug testing using liquid chromatography-mass spectrometry or gas chromatography-mass spectrometry in exposed first responders. Among first responders possibly exposed to fentanyl or fentanyl analogs, none were admitted to the hospital, and only three first responders received naloxone. The three officers who received naloxone lacked recommended personal protective equipment and had subjective improvement of symptoms following naloxone. There were no instances of severe respiratory depression requiring assisted ventilation or hospital admission. Among forensic laboratory technicians, only one instance of detectable concentrations of fentanyl in urine was reported, and there were no instances of symptomatic cases. Among published reports of 27 first responders with symptoms after possible ambient fentanyl exposure, symptoms, recorded physical findings, and vital signs were inconsistent with acute opioid toxicity. Breaches in the recommended use of personal protective equipment appeared common. Only three persons received naloxone, although none had plausible effects of fentanyl. No suspected exposure to fentanyl led to hospitalization or death. Based on these low-quality data, there were no plausible opioid effects from ambient exposure to suspected fentanyl.